The Objective of this Study is to Examine the Relationship Between Nurses' Knowledge Levels of Patient Safety Identification and the Implementation of These Practices in Hospitals - Lamria Situmeang; Sumarmi; Sulistiyani; Samsir (CV. Get Press Indonesia, 2024)
Patient safety is one of the main components in improving the quality of health services (Permatha Indah et al., 2022). Patient safety includes a series of actions aimed at preventing injury or unwanted complications during the care process (Sari, 2020; Sitepu, 2020; (Oktiana Tamba, 2020). This study aims to explore the relationship between nurses' level of knowledge about identification in patient safety and the implementation of these procedures in the inpatient room. This study used a descriptive correlational design with a quantitative approach. This design was chosen to determine the relationship between nurses' level of knowledge about identification in patient safety and the implementation of this identification in the inpatient room. Most respondents have a fairly good level of knowledge as many as 50 people (78.1%), while only 14 people (21.9%) have good knowledge. based on the implementation of identification in patient safety is quite good as many as 51 people (79.7%), while only 13 people (20.3%) carry out well. The p-value of 0.0001 indicates a significant relationship between the level of knowledge of nurses about identification in patient safety with the implementation of identification in patient safety. Understand the importance of effective education and training to improve knowledge and implementation of identification, which ultimately aims to improve patient safety.